Effectiveness of Respiratory Muscle Training Interventions in Patients with Spinal Cord Injury; A Literature Review - Pratiwi, Sri Hartati; Handayani, Nathasa (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2023)
Spinal Cord Injury (SCI) level tinggi dapat menyebabkan gangguan pada pernapasan yang dapat mengancam nyawa pasien. One of the interventions that can be given to individuals with SCI in reducing complications of respiratory problems is Respiratory Muscle Training (RMT). Respiratory Muscle Training (RMT) is a technique that aims to improve the function of the respiratory muscles through specific exercises. This study determined the effectiveness of respiratory muscle training in spinal cord injury patients with respiratory problems. This literature review used several databases such as Google Scholar, Pubmed, Ebsco, Sciencedirect, CINAHL, and SAGE with inclusion criteria Articles published less than five years (2018-2022), English, Full text, Systematic review/meta-analysis/RCT. The results indicate that this RMT intervention's effectiveness on respiratory muscles and lung function depends on the characteristics of SCI patients. There were six articles used for the review of this paper. The results show that this respiratory muscle training intervention's effectiveness impacts respiratory muscles and lung function depending on the characteristics of the spinal cord injury patient himself. Furthermore, the results suggest that this RMT intervention's efficacy on respiratory muscle and lung function depends on the features of the SCI patient